Integration of Top Down And Bottom Up Approaches in Efforts To Handle Stunting in Yogyakarta City - Nuha Banin Darajatin Aliyah (Dinasti International Journal of Education Management And Social Science, 2025)
Addressing stunting requires a comprehensive approach that integrates central government policies with local initiatives. This study aims to analyze the implementation of integrated top-down and bottom-up approaches in stunting prevention programs in Yogyakarta City. The research method uses a qualitative approach with library research, analyzing policy documents and stunting program reports from 2020-2024. The results show successful integration of approaches through reduced stunting prevalence from 13.8% (2022) to 10.6% (2024). This success is supported by an integrated governance system, multi-stakeholder collaboration, and local wisdom-based program innovations. Yogyakarta City's stunting management model can serve as a reference for other regions while considering their local contexts.